Recognizing Age at Slaughter of Cattle from Beef Samples Using Gc/Ms-Spme Chromatographic Method - Silva-Serrano, J; Tomic-Stefanin, G; Santander-Meyer, R (2013)
Beef from cattle less than 30 months old at the point of slaughter are generally sold in meat markets. Though the age of the animal can generally be estimated by dentition, this method cannot be applied to a carcass or a piece of meat from which the teeth have been removed. Since gas chromatography of volatile organic compounds has been used to classify biological samples, this technique was used for classifying meat obtained from cattle aged over 30 months (OTM) at point of slaughter. Volatile organic compounds of fresh meat (M. longissimus dorsi) samples obtained from cattle of different age and dentition (two, four, and six teeth) at point of slaughter were analyzed using gas chromatography/mass spectrum (GC/MS). Six volatile organic compounds were selected (hexanoic acid, benzoic acid, octanoid acid, tridecane, tetradecane, and 4-formylbenzoic acid) and confirmed by using chemical standards and Kovat s indexes. The chromatogram data were used to train two classifiers, one based on the partial least square (PLS) method and another based on support vector machine (SVM), but only SVM showed high accuracy. Data exploration based on the principal component analysis allowed for comprehension of the data distribution, proposing a new version of PLS in a parallel configuration. This modified version of the PLS algorithm showed better accuracy than the SVM classifier. In conclusion, volatile organic compounds analyzed by GC/MS-solid-phase microextraction can be used to recognize OTM beef. © 2012 Springer Science+Business Media New York.